The association between activity levels and skin moisturising function in adults - Ryosuke Oizumi; Yoshie Sugimoto; Hiromi Aibara (PAGEPress Publications, 2021)
Factors associated with skin moisture retention include age and lifestyle, such as diet and sleep efficiency. However, the impact of exercise habits on skin moisturising function is unclear. We surveyed 86 participants from a Japanese university about their activity levels using the International Physical Activity Questionnaire. We also examined their skin moisturising function, measuring stratum corneum (SC) hydration levels and transepidermal water loss (TEWL). Comparisons of participants' activity levels, SC hydration, and TEWL, accounting for their gender and age differences, revealed activity levels significantly related to differences in SC hydration levels. Results of multiple comparisons showed increased activity relates to significantly higher SC hydration − the higher the activity levels, the higher the hydration. No difference was found in TEWL. The results suggest exercise habits can prevent dry skin. The findings may be useful for the prevention and treatment of dry skin and promoting the benefits of exercise.